Healthcare Provider Experiences With Unvaccinated COVID-19 Patients: A Qualitative Study - Candice Griffin, MD; Christie Lee, MSc, MD; Phil Shin, MSc, MD; Andrew Helmers, MHSc, MD; Csilla Kalocsai, MPhil, PhD; Allia Karim; Dominique Piquette, MSc, MD, PhD (Critical Care Explorations, 2024)
IMPORTANCE:. In the setting of an active pandemic the impact of public vaccine hesitancy on healthcare workers has not yet been explored. There is currently a paucity of literature that examines how patient resistance to disease prevention in general impacts practitioners. OBJECTIVES:. The COVID-19 pandemic created unprecedented healthcare challenges with impacts on healthcare workers’ wellbeing. Vaccine hesitancy added complexity to providing care for unvaccinated patients. Our study qualitatively explored experiences of healthcare providers caring for unvaccinated patients with severe COVID-19 infection in the intensive care setting. DESIGN:. We used interview-based constructivist grounded theory methodology to explore experiences of healthcare providers with critically ill unvaccinated COVID-19 patients. SETTING AND PARTICIPANTS:. Healthcare providers who cared for unvaccinated patients with severe COVID-19 respiratory failure following availability of severe acute respiratory syndrome coronavirus 2 vaccines were recruited from seven ICUs located within two large academic centers and one community-based hospital. We interviewed 24 participants, consisting of eight attending physicians, seven registered nurses, six critical care fellows, one respiratory therapist, one physiotherapist, and one social worker between March 2022 and September 2022 (approximately 1.5 yr after the availability of COVID-19 vaccines in Canada). ANALYSIS:. Interviews were recorded, transcribed, de-identified, and coded to identify emerging themes. The final data was analyzed to generate the thematic framework. Reflexivity was employed to reflect upon and discuss individual pre-conceptions and opinions that may impact collection and interpretation of the data. RESULTS:. Healthcare providers maintained dedication toward professionalism during provision of care, at the cost of suffering emotional turmoil from the pandemic and COVID-19 vaccine hesitancy. Evolving sources of stress associated with vaccine hesitancy included ongoing high volumes of critically ill patients, resource shortages, and visitation restrictions, which contributed to perceived emotional distress, empathy loss, and professional dissatisfaction. As a result, there were profound personal and professional consequences for healthcare professionals, with perceived impacts on patient care. CONCLUSIONS:. Our study highlights struggles of healthcare providers in fulfilling professional duties while navigating emotional stressors unique to vaccine hesitancy. System-based interventions should be explored to help providers navigate biases and moral distress, and to foster resilience for the next major healthcare system strain.